(untitled) (Medical Forum Monthly, 2022)
Objective: To find the effectiveness of chlorhexidine gel alone and with combination with metronidazole use as intra socket substance to prevent alveolar osteitis. Study Design: Prospective observational study Place and Duration of Study: This study was conducted at the oral and maxillofacial surgery department of the Islam Dental College Sialkot from Jan, 2021 to Dec, 2021. Materials and Methods: 100 patients that were undergone surgical extractions, included in this study. Even and odd pattern used to segregate 100 patients into group A with odd number and group B with even number. Immunocompetent patients with age less than 50 years, no co-morbidities and without involvement of odontogenic space infection cases were included in this study. Group A patients were advised to use chlorhexidine gel post-surgical extraction as intra socket medicament and Group B patients were advised to use chlorhexidine gel with combination of metronidazole (Revomet plus gel). On 3rd post extraction day, visual analog scale was used to document. Pain and clinically observed empty socket feature were used to label as alveolar osteitis cases. Results: Female to male ratio was 1.6:1. Total incidence of alveolar osteitis was 20% (n=20). 24% (n=12) cases were observed in group A and 16% (n=8) cases were observed in group B. Among group A, 29 cases had mild pain, 9 had moderate and 6 had severe pain. While in group B, 23 cases had mild pain, 8 cases had severe pain and 4 cases had severe pain. Overall moderate and severe pain with empty socket cases were high in group A those had used chlorhexidine gel as intra socket medicament. Conclusion: The prophylactic usage of combination of chlorhexidine with metronidazole gel (REVOMET PLUS GEL) in reducing the incidence of dry socket is better than chlorhexidine gel alone.